Fighting the fire [videorecording (DVD)] - Lacer, Bobby, 1973-; Dickey, James, (Actor); Baker, Angela Katherine, 1981-; Lacer, Brayden, 2005-; Kemp, Kaitlyn (Burning Bulb Productions, 2024)
Brian Cook has served bravely as a firefighter for over 15 years. He loves his career and has a wonderful wife, two amazing kids, and great friends who love and support him. Basically, he has it all. Until one emergency run changes everything. Brian can't seem to let go of the horrific event and begins to internalize it and other tragedies he has witnessed during his time with the fire service. As Brian slips deeper into depression, he begins to self-medicate and pushes everyone away. He now faces the biggest battle of his life not the fire in the field, but the fire burning inside. Will he seek the help he needs from those who love him before it is too late and he loses everything?